Insulin resistance: the linchpin between prediabetes and cardiovascular disease - Salazar, Martín R. (2016)
The aim of this study was to test the hypothesis that cardiovascular disease occurs to the greatest extent in persons with prediabetes mellitus who are also insulin resistant. In 2003, 664 non-diabetic women (n = 457) and men (n = 207), aged 52 ± 16 and 53 ± 15 years, were surveyed during a programme for cardiovascular disease prevention. Fasting plasma glucose concentrations defined participants as having normal fasting plasma glucose (fasting plasma glucose <5.6 mmol/L) or prediabetes mellitus (fasting plasma glucose ⩾ 5.6 and <7.0 mmol/L). The tertile of prediabetes mellitus subjects with the highest fasting plasma insulin concentration was classified as insulin resistant. Baseline cardiovascular disease risk factors were accentuated in prediabetes mellitus versus normal fasting glucose, particularly in prediabetes mellitus/insulin resistant. In 2012, 86% of the sample were surveyed again, and the crude incidence for cardiovascular disease was higher in subjects with prediabetes mellitus versus normal fasting glucose (13.7 vs 6.0/100 persons/10 years; age- and sex-adjusted hazard ratio = 1.88, p = 0.052). In prediabetes mellitus, the crude incidences were 22.9 versus 9.6/100 persons/10 years in insulin resistant versus non-insulin resistant persons (age- and sex-adjusted hazard ratio = 2.36, p = 0.040). In conclusion, cardiovascular disease risk was accentuated in prediabetes mellitus/insulin resistant individuals, with a relative risk approximately twice as high compared to prediabetes mellitus/non-insulin resistant subjects.